Economische betrekkingen tussen Hongarije en de Lage Landen in de Middeleeuwen Abstract - Pósán, László (Acta Neerlandica, 2015)
In spite of the remarkable distance and the expenses incurred in transportation through a number of go-betweens Hungarian (primary) commodities and products from the Low Countries found their way to each other’s markets. The present study makes an inquiry into these trade relations in which it was primarily Prussian and southern German traders, especially of Nuremberg, who played a dominant role. Copper and prescions metals were the most important commodities shipped to the markets ot Flanders from Hungary by Prussian tradesmen via Poland and the Baltic Sea. Hungary exported iron and zinc to the Low Countries and also beeswax and hides and furs. It was mainly cloth that was imported into Hungary from the markets in Flanders roughly along the same trade route as the one along which commodities from Hungary found their way to the Atlantic coastal areas, that is, via the Baltic Sea and Poland. The volume and value of the export goods from medieval Hungary surpassed that of the import goods from the Low Countries, for the latter was made up of finished products of high quality and high prices therefore targeted only a limited high-end range of customers and their volume was thus less remarkable. The products of the two areas reached their respective destinations by means of a chain of intermediaries.